Transitioning Pedagogies: Baby Boomer Educators’ Adaptation From Chalkboard To New Technology - Dizon, Cyra; Del Rosario, Ligaya; Operario, Marissa; de Castro, Luningning; Buhain, Vivian; Tabunda, Dorislyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined Baby Boomer educators’ lived experiences as they transitioned from traditional chalkboard-based instruction to technology-integrated teaching amid rapid digital transformation in education. Anchored in the Theory of Reasoned Action (TRA), the Technological Pedagogical Content Knowledge (TPACK) framework, and the Technology Acceptance Model (TAM), the study explored how educators made meaning of technological change and how perceived usefulness and ease of use shaped their adaptation. Using a qualitative, transcendental phenomenological design, data were gathered through semi-structured interviews supported by field notes, classroom observations, and document review. Respondents were Baby Boomer educators (ages 61–79) selected through purposive sampling from institutions in Quezon City, Bulacan, and Paranaque. The findings indicate varied baseline digital proficiency, but consistent willingness to learn, with educators gradually adopting tools such as PowerPoint, Canva, Moodle, Google Classroom, Kahoot, and Quizziz. Participants described the transition as initially difficult due to limited time, unfamiliarity with software, and anxiety about technical issues, while systemic barriers such as inconsistent internet access and unequal device availability also constrained implementation. Despite these challenges, educators reported coping through self-directed learning, peer collaboration, and available institutional or external support, and they perceived technology integration as improving lesson delivery, reducing some administrative burdens, and increasing student engagement and participation. The study concludes that bridging infrastructural gaps and strengthening continuous professional support are essential to sustaining inclusive technology integration. The study aligns with SDG 4 – Quality Education through its focus on teacher capability-building and effective digital pedagogy, and with SDG 9 – Industry, Innovation and Infrastructure by highlighting the role of connectivity and digital systems in educational transformation. In sustainability terms, the study contributes to educational and institutional sustainability by emphasizing that technology-enabled learning becomes sustainable only when supported by training, equitable access, and collaborative cultures that prevent widening generational and resource-based inequalities.